Measurements of hydroxyl and hydroperoxy radicals during CalNex‐LA: Model comparisons and radical budgets. Issue 8 (21st April 2016) - Griffith, S. M.; Hansen, R. F.; Dusanter, S.; Michoud, V.; Gilman, J. B.; Kuster, W. C.; Veres, P. R.; Graus, M.; de Gouw, J. A.; Roberts, J.; Young, C.; Washenfelder, R.; et al.
Abstract: Measurements of hydroxyl (OH) and hydroperoxy (HO2 *) radical concentrations were made at the Pasadena ground site during the CalNex‐LA 2010 campaign using the laser‐induced fluorescence‐fluorescence assay by gas expansion technique. The measured concentrations of OH and HO2 * exhibited a distinct weekend effect, with higher radical concentrations observed on the weekends corresponding to lower levels of nitrogen oxides (NOx ). The radical measurements were compared to results from a zero‐dimensional model using the Regional Atmospheric Chemical Mechanism‐2 constrained by NOx and other measured trace gases. The chemical model overpredicted measured OH concentrations during the weekends by a factor of approximately 1.4 ± 0.3 (1 σ ), but the agreement was better during the weekdays (ratio of 1.0 ± 0.2). Model predicted HO2 * concentrations underpredicted by a factor of 1.3 ± 0.2 on the weekends, while measured weekday concentrations were underpredicted by a factor of 3.0 ± 0.5. However, increasing the modeled OH reactivity to match the measured total OH reactivity improved the overall agreement for both OH and HO2 * on all days. A radical budget analysis suggests that photolysis of carbonyls and formaldehyde together accounted for approximately 40% of radical initiation with photolysis of nitrous acid accounting for 30% at the measurement height and ozone photolysis contributing less than 20%. An analysis of the ozone production sensitivity reveals that during the week, ozone production was limited by volatile organic compounds throughout the day during the campaign but NOx limited during the afternoon on the weekends. Key Points: Measurements of OH and HO2 during CalNex‐LA displayed a weekend effect Modeled OH and HO2 agreed with measurements after accounting for missing OH reactivity Ozone production was VOC limited on the weekdays but NOx limited on the weekends